Synergizing Innovation: Examining the TOE Readiness Influence, Ambidextrous Capabilities, Organization Resilience on Craft SMEs - Etwin Fibrianie Soeprapto; Sri Gunani Partiwi; Retno Widyaningrum (Ital Publication, 2026)
This study examines how technology-organization-environment (TOE) readiness (TR), ambidextrous organization (AO), and organizational resilience (OR) influence innovation performance (IP) and competitive advantage (CA) in small and medium-sized enterprises (SMEs), focusing on craft-based firms operating in dynamic and uncertain environments. A quantitative research design was chosen to collect survey data from 200 Indonesian craft-based SME owners and managers. Structural equation modelling (SEM) was employed to analyze the data and examine both direct and indirect relationships among the proposed constructs. The findings demonstrate that TR, AO, and OR each have a significant positive effect on IP. In turn, IP has a strong positive effect on CA, highlighting its key role in converting organizational capabilities into market success as well as a complementary mediating mechanism linking TR, AO, and OR to competitive outcomes. The novel contribution of this study is the empirical integration of TR with internal dynamic capabilities, namely AO and OR, in a single structural model that explains how SMEs transform innovation-related capabilities into CA. This integrative perspective contributes to the literature on SME innovation and offers practical implications for managers and policymakers seeking to strengthen innovation-driven competitiveness and long-term sustainability amid turbulent environmental conditions in emerging market contexts.